A sportomics strategy to analyze the ability of arginine to modulate both ammonia and lymphocyte levels in blood after high-intensity exercise - Goncalves, L.; Bessa, A.; Freitas-Dias, R.; Luzes, R.; Werneck-de-Castro, J.; Bassini, A.; Cameron, L. (Journal of the International Society of Sports Nutrition, 2012)
Exercise is an excellent tool to study the interactions between metabolic stress and the immune system. Specifically, high-intensity exercises both produce transient hyperammonemia and influence the distribution of white blood cells. Carbohydrates and glutamine and arginine supplementation were previously shown to effectively modulate ammonia levels during exercise. In this study, we used a short-duration, high-intensity exercise together with a low carbohydrate diet to induce a hyperammonemia state and better understand how arginine influences both ammonemia and the distribution of leukocytes in the blood. Methods: Brazilian Jiu-Jitsu practitioners (men, n = 39) volunteered for this study. The subjects followed a low-carbohydrate diet for four days before the trials and received either arginine supplementation (100 mg.kg-1 of body mass.day-1) or a placebo. The intergroup statistical significance was calculated by a one-way analysis of variance, followed by Student's t-test. The data correlations were calculated using Pearson's test. Results: In the control group, ammonemia increased during matches at almost twice the rate of the arginine group (25 mmol.L-1.min-1 and 13 mumol.L-1.min-1, respectively). Exercise induced an increase in leukocytes of approximately 75%. An even greater difference was observed in the lymphocyte count, which increased 2.2-fold in the control group; this increase was partially prevented by arginine supplementation. The shape of the ammonemia curve suggests that arginine helps prevent increases in ammonia levels. Conclusions: These data indicate that increases in lymphocytes and ammonia are simultaneously reduced by arginine supplementation. We propose that increased serum lymphocytes could be related to changes in ammonemia and ammonia metabolism.